PRODUCTIVE AND ECONOMIC RESPONSE OF GUINEA PIGS TO THE USE OF FOUR TYPES OF DRINKERS AND THE ADDITION OF VITAMIN C DURING THE DRY SEASON IN THE MANTARO VALLEY - Sánchez V., Raúl (2013)
The study evaluated the effect of four types of drinkers and the addition of Vitamin C in the supplement on the productive performance and economic benefit of guinea pig (Cavia porcellus) reared during the dry season in the Mantaro valley, Junin, Peru. Four hundred weaned males, 14 ± 3 days of age from the experimental farm of the IVITA Research Centre were used in a completely randomized design with 2 x 4 arrangement factorial (with and without addition of vitamin C and four types of drinkers) using five experimental units for treatment and every experimental unit formed by 10 animals. The drinkers were the type of a bowl (POC), continuous recharge (REC), suction (SUC) and nipple (NIP). The quantity of vitamin C supplied was 12 mg/animal/day. REC and NIP drinkers allowed a major consumption of water than POC and SUC (p<0.05), but REC had a greater waste of water. A similar trend was observed for feed intake, body weight gain, feed conversion index, and in the benefit/cost ratio. The addition of vitamin C only improved the intake (p<0.05). The study concluded that the NIP and REC drinkers are the most suitable for rearing guinea pigs during the dry season in relation to productive performance and NIP for economic benefit.